Solusi Hukum Mengatasi Masalah Menumpuknya Perkara di Tingkat Kasasi Mahkamah Agung RI (Usulan Perubahan Kelima UUD RI Tahun 1945) - Lufsiana (Faculty of Law Hang Tuah University, 2017)
The accumulation of cases at the Cassation level of the Supreme Court of the Republic of Indonesia has not been resolved, even though there are internal rules that determine the deadline for case settlement for 250 days and the distribution of rooms in the environment of the Supreme Court of the Republic of Indonesia. violating the legal principle of the administration of simple, fast and low-cost justice has even opened the door of corruption, because justice seekers will try to accelerate to get a verdict on the case. This paper provides a legal solution to the problem, namely by forming a representative of the Supreme Court of Indonesia in every province in Indonesia and empowering the nation's children to become Supreme Court Justices (opening employment opportunities that are wide enough for legal professionals) by using the legislation approach.